Constitución sin constitucionalismo. El problema sobre límites y control del poder en el poder constitucional y la democracia de derechos en el Ecuador - Córdova Vinueza , Paúl (2016)
Why legal reasons the 2008 Constitution is characterized by the concentration and centralization of power? and What are the structural factors that undermine the development of a constitutional democracy and iusfundamentales rights? From these questions, the author considers that the existence of a powerful hyper-presidentialism reduces the formation of a system of institutional checks and balances balanced and fracture separation of powers to the full force of a republican state. In response, it maintains that controls and limits on the power are the pending challenge of the ecuadorian constitutionalism.